Gambaran Pengetahuan Ibu Tentang Stunting Pada Balita Di Pekanbaru - adde Febriani (LPPM Universitas Abdurrab, 2023)
Stunting is the nutritional status that befalls children whose height or length is below -2.0 standard deviation (SD) if a comparison is made to the population average. Insights that parents have regarding the symptoms, the effects that arise, including the prevention of stunting can be a determinant of their attitude in maintaining health so that stunting can be prevented. If the insight is good, parents' awareness of the urgency of handling stunting will be visible. This awareness will lead to health behavior, especially regarding stunting prevention, for example through fulfilling nutrition for pregnant women, nutrition for children, maintaining sanitation in the home environment, including a clean and healthy lifestyle. This study used a descriptive method with a cross-sectional approach. Where research measures or observes variable data only once at a time. The sample in this study were mothers who had toddlers aged 0-5 years, there were 65 mothers with toddlers. The aim of the researcher is to identify the description of mother's knowledge about stunting in toddlers. The results showed that the average age of 65 respondents who were mothers of toddlers who lived in Pekanbaru was the late adult age of 20-35 years, which was 75.4%. high school education with a total of 66.2%. And most mothers of toddlers do not work with a total of 66.2, sufficient knowledge about stunting in toddlers with a total of 46.1%. The recommended suggestion for further research is to develop research with a cross-sectional research design in order to further identify the relationship between the sub-variables of the characteristics of mothers having toddlers in relation to knowledge of stunting in toddlers.